Pulmonary and Inspiratory Muscle Function Response to a Mountain Ultramarathon - Ignacio Martinez-Navarro, Eladio Collado, Bárbara Hernando, Carlos Hernando (Journal of Sports Science and Medicine, 2021)
The study aimed to provide within-race data on the time course of pulmonary function during a mountain ultramarathon (MUM). Additionally, we wanted to assess possible sex differences regarding pre- to post-race change in pulmonary and inspiratory muscle function. Lastly, we were interested in evaluating whether changes in respiratory function were associated with relative running speed and due to general or specific fatigue. 47 athletes (29 males and 18 females; 41 ± 5 years) were submitted to a cardiopulmonary exercise test (CPET) before a 107-km MUM. Spirometric variables: forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC and peak expiratory flow (PEF); maximal inspiratory pressure (MIP); squat jump (SJ) and handgrip strength (HG) were assessed before and after the race. Additionally PEF was measured at three aid stations (33rd, 66th and 84th km) during the race. PEF declined from the 33rd to the 66th km (p = 0.004; d = 0.72) and from the 84th km to the finish line (p = 0.003; d = 0.90), while relative running speed dropped from the first (0-33 km) to the second (33-66 km) race section (p < 0.001; d = 1.81) and from the third (66-84 km) to the last race section (p < 0.001; d = 1.61). Post-race, a moderate reduction was noted in FVC (-13%; p < 0.001; d = 0.52), FEV1 (-19.5%; p < 0.001; d = 0.65), FEV1/FVC (-8.4%; p = 0.030; d = 0.59), PEF (-20.3%; p < 0.001; d = 0.58), MIP (-25.3%; p < 0.001; d = 0.79) and SJ (-31.6%; p < 0.001; d = 1.42). Conversely, HG did not change from pre- to post-race (-1.4%; p = 0.56; d = 0.05). PEF declined during the race in parallel with running speed drop. No sex differences were noted regarding post-race respiratory function, except that FEV1/FVC decay was significantly greater among women. The magnitude of pre- to post-race respiratory function decline was uncorrelated with relative running speed.